The great leprechaun chase - Dean, James 1957-
When Pete the Cat opens a leprechaun catching business on St. Patrick's Day, his efforts are complicated by Clover, a leprechaun who's full of tricks
Keywords: Pete / the Cat (Fictional character) / Fiction; Cats / Juvenile fiction; Leprechauns / Juvenile fiction; Saint Patrick's Day / Juvenile fiction; Picture books for children; Cats / Fiction; Leprechauns / Fiction; St. Patrick's Day / Fiction; JUVENILE FICTION / Holidays & Celebrations / General (see also Religious / Christian / Holidays & Celebrations); JUVENILE FICTION / Humorous Stories; JUVENILE FICTION / Animals / Cats; Cats; Leprechauns; Saint Patrick's Day; Saint Patrick's Day / Fiction; Bilderbuch